Nutraceuticals in Ayurveda w.s.r to Yavagu: A Review Article - Sharma, Rina; Gupta, Nisha; Sharma, Vidhya bharti; Singh, Usha (International Research Journal of Ayurveda & Yoga, 2020)
In Ayurveda science, root cause of diseases is explained by the concept of mandagani. So in Ayurveda classical literature Acharya firstly focused on diet because due to faulty food habits digestive power can be hampered. In samhitas Acharya explained diet of any individual at many places with their nutritional and pharmacological properties. So in some cases patient can be cured only with the proper food recipes. Yavagu are simple recipes with great nutritional as well as pharmacological properties which depends on the drug used to prepare the recipe thus these yavagu kalpana should be considered as nutraceuticals.